Crisis communication in the atomic sector: protocol, characteristics, and recommendations in nuclear events - Cobos Urbina, Enrique; Recoder Sellarés, María José (Revista Española de Comunicación en Salud, 2019)
Nuclear power plants need an organized communication for the two types of special situations they face: on the one hand to inform relevant stakeholders of what is happening in an operational crisis; and on the other hand to recover public confidence in those unforeseen events that affect the reputation of the nuclear power plant and the social legitimacy of nuclear energy. What characteristics define nuclear crisis communication? What communicative protocol is followed in Spain in case of a nuclear accident or incident? Are the theories of strategic communication taken into account during periods of crisis?
Keywords: nuclear power plants; nuclear energy; crisis communication; nuclear communication; Spain